THIRD MOLAR IMPACTION AS A PREDISPOSING FACTOR IN ANGLE OF MANDIBULAR FRACTURE - A RETROSPECTIVE ANALYSIS - Suresh Babu, Priyadharshini; Jayaraj, Gifrina; Mani, Geo (International Journal of Psychosocial Rehabilitation, 2020)
Aim: The mandibular angle and condylar region are most prone to fracture, and this has been attributed to the presence and absence of the third molar. There was a definitive positive relation between impacted third molar and increased incidence of angle fractures. Third molar impaction acts as a predisposing factor to angle fracture. The aim of the study is to investigate the effect of third molar impaction on the mandible angle fracture. Materials and methods: The study retrospectively analyzed the clinical and radiographic findings of the patients with the angle of mandibular fracture during the time period of June 2019 to March 2020 by reviewing 86,000 patient records of those who visited Saveetha Dental College in Chennai. The total sample of mandibular angle fracture obtained was 19. The data was tabulated and entered in Excel. Chi-square analysis was done using SPSS package software. The variable impact of the third molar and side of the mandibular angle fracture was compared. In the study, p<0.05 was considered to be the level of statistical significance. Results: Among the 77 maxillofacial fracture data collected, only 62.3% of the fractures were found to be mandibular fractures. The fracture that occurred in the angle region of the mandible was 44.1%. 31.6% of the third molars were impacted, whereas 68.4% were non-impacted teeth. There is a higher incidence of mandibular fractures in males compared to that of females. The most common age group was 31-40 years. A chi-square test was done, and the p-value obtained was 0.252, which is >0.05. There was no significant difference between the presence of an impacted third molar and an angular fracture of the mandible. Conclusion : In this study it is observed that the mandibular fracture is more prevalent in males with right mandibular angle fractures in both impacted lower third molars. The presence of a third molar contributes to the increased mandibular fragility, which leads to mandibular fracture.